Effect of Pomegranate Seed oil on the Urinary System (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Pomegranate seed oil, obtained by cold pressing the seeds of the fruit, has long been used in traditional medicine and is noteworthy for its potential health benefits. Regarding its effect on the urinary system, there are several aspects: Diuretic Properties: Pomegranate seed oil has mild diuretic properties, which means it may help increase urine output. This may be helpful for people suffering from swelling or discomfort associated with fluid retention. Anti-inflammatory properties: Components of pomegranate seed oil, such as phytochemicals and antioxidants, may help reduce inflammation in the urinary system. This may be especially useful for various conditions such as cystitis or other inflammatory conditions. Kidney protection: Some research suggests that the antioxidants found in pomegranate seed oil may help protect kidney tissue from damage caused by oxidative stress. This may help maintain kidney health and prevent the development of certain kidney diseases.